Smoking Status Effect on Inflammatory Markers in a Randomized Trial of Current and Former Heavy Smokers - Sami Aldaham; Janet A. Foote; H.-H. Sherry Chow; Iman A. Hakim (Hindawi Limited, 2015)
Background. The level of systemic inflammation as measured by circulating levels of C-reactive protein (CRP) and interleukin-6 (IL-6) is linked to an increased risk for cardiovascular diseases (CVD) and cancer. Methods. We recruited 154 current and former smokers between 40 and 80 years of age with 25 or more pack-years of smoking history to study the relationship between inflammatory markers (CRP and IL-6) and smoking status. Results. Our results show that male smokers had significantly higher levels of serum IL-6 compared to male former smokers. We did not find any gender specific differences for smoking and CRP levels but the IL-6 levels were slightly lower in females compared to males. Additionally, our results show that CRP is significantly associated with IL-6 regardless of smoking status. Modelling indicates that the significant predictors of CRP levels were biomarkers of the metabolic syndrome while the significant predictors of IL-6 levels were age and plasma triglycerides among former smokers and the numbers of smoked packs of cigarettes per year among smokers. Conclusions. In conclusion, our study showed that CRP levels were not associated with markers of smoking intensity. However, IL-6 levels were significantly associated with smoking especially among current smokers.